The Influence of Lohas and Consumer Effectiveness on Organic Food Purchase Intention: Trust as a Mediator - Kimartha Putri; Yusup, Adi Kurniawan (Journal of Global Business and Management Review, 2024)
A sustainable lifestyle has evolved since COVID-19, influencing the growth of organic food consumption in Indonesia. This growth is driven by various factors, primarily related to health and environmental concerns. This study aims to analyze the organic food purchasing intentions of Bali residents using the variables of LOHAS Consumption Tendency (LCT) and Perceived Consumer Effectiveness (PCE), with trust as a mediating factor. The Theory of Planned Behavior (TPB) is applied to formulate the hypotheses. A quantitative method is employed, with data collected through questionnaires distributed to the target respondents. The total sample consists of 205 respondents aged 18 and above, residing in Bali. SEM-PLS is used for data analysis, revealing that LCT and PCE positively impact organic food purchase intention, LCT and PCE positively impact trust, and trust has a positive effect on organic food purchase intention, serving as a mediator between LCT, PCE, and organic food purchase intention.